A feasibility study to introduce modern city buses for intra city operations by the year 2000 / Ahmad Khairul Mohd Khusairi - Mohd Khusairi, Ahmad Khairul (1994)
The city of Kuala Lumpur is the centre of business, commercial and administrative activities. For the last two decades, this city has experienced heightening problem of traffic congestion. Every year, the number of motor vehicles entering KL are on the rise. Most of these are single occupancy vehicles which reduce road space and hence limit the usage of other modes of transport. Due to this circumstances, stage buses as another form of transportation, are having less ridership which have an effect on the quality of services provided. This research looks into the feasibility aspects of using modern buses in the city of KL in an effort to bring about better services so much so that the public are more willing to use them instead of using their cars to commute to KL.